BEYOND ENERGY: THE ROLE OF COLONIAL LEGACY IN THE EFFECT OF INSTITUTIONAL QUALITY ON RENEWABLE ENERGY CONSUMPTION IN WEST AFRICA - Musa Ilias Biala; Ololade Mistura Aromasodun (Malete Journal of Accounting and Finance)
A stable institutional framework and colonial legacy are essential for ensuring environmental quality and economic growth. However, recent studies have overlooked these critical factors despite their significance. This study, therefore, explored the impact of institutional quality on renewable energy consumption in West Africa from 1990 to 2023 with a novel incorporation of the influence of colonial legacy. Using data from the World Bank’s World Development Indicator, this study utilised the Pooled Mean Group technique. The study found that in the long run, GDP per capita, carbon dioxide emissions and urbanisation had a significant negative impact on renewable energy consumption whereas technology, institutional quality, and the interaction of institution with colonial legacy had a significant positive impact on renewable energy consumption. To achieve sustainable development, the study recommends that policy makers prioritise institutional stability while leveraging technological advancements to promote renewable energy production. Policymakers and international organisations should consider the unique historical and institutional context of West African countries while designing renewable energy policies and programmes.